Lower Oil Prices and the U.S. Economy: Is this Time Different? - Christiane Baumeister; Lutz Kilian (Center for Economic Studies and ifo Institute (CESifo), 2017)
We explore the effect on U.S. real GDP growth of the sharp and sustained decline in the global price of crude oil and hence in the U.S. price of gasoline after June 2014. Our analysis suggests that this decline produced a cumulative stimulus of about 0.9 percentage points of real GDP growth by raising private real consumption and non-oil related business investment and an additional stimulus of 0.04 percentage points reflecting a shrinking petroleum trade deficit. This stimulating effect, however, has been largely offset by a large reduction in real investment by the oil sector. Hence, the net stimulus since June 2014 has been close to zero. We show that the response of the U.S. economy was not fundamentally different from that observed after the oil price decline of 1986. Then as now the response of the U.S. economy is consistent with standard economic models of the transmission of oil price shocks. We found no evidence of an additional role for frictions in reallocating labor across sectors or for increased uncertainty about the price of gasoline in explaining the sluggish response of U.S. real GDP growth. Nor did we find evidence of financial contagion, of spillovers from oil-related investment to non-oil related investment, of an increase in household savings, or of households deleveraging.
Keywords: E32; Q43; 330; stimulus; oil price decline; uncertainty; reallocation; savings; shale oil; oil loans